Fatigue behaviour of inkjet-printed silver interconnects on silica-coated mesoporous flexible PET substrate. (1st March 2022) - Khinda, Gurvinder Singh; Kokash, Maan Z; Alhendi, Mohammed; Garakani, Behnam; Stoffel, Nancy C; Borgesen, Peter; Poliks, Mark D
Abstract: Inkjet-printed silver conductive patterns are used in many flexible electronics applications ranging from health care, industrial assets management to aviation. Understanding of the electrical behaviour of these printed patterns under different mechanical stresses and environmental conditions is important for their real-life application use. The present work addresses a special system, silver interconnects on silica-coated mesoporous polyethylene terephthalate (PET) substrate. The combination of the substrate porosity and roughness, and a sintering temperature limited by the low glass transition temperature ( T g ) of the PET leads to unique behaviours that may easily be misinterpreted. Thus, while the interconnect resistance increases during stretching and decreases with unloading, the resistance at zero load is lower after a given cycle than before it and it continues to drop in consecutive cycles. This effect is stronger for higher strain amplitudes, but it could be reduced or eliminated by preceding low temperature annealing. Humidity exposure and thermal cycling also led to major drops in resistance, albeit for different reasons, but both led to faster fatigue in subsequent mechanical deformation. Accounting for these behaviours in the assessment of life under realistic use conditions requires a mechanistic understanding.